Changes in transcranial electrical motor-evoked potentials during the early and reversible stage of permanent spinal cord ischemia predict spinal cord injury in a rabbit animal model - Wang, Mingguang (Exp Ther Med, 2017)
The present study examined changes in the transcranial electrical motor-evoked potentials (TceMEP) waveform to predict neurological deficits and histopathological changes during the early and reversible stage of different levels of permanent spinal cord ischemic injury in a rabbit animal model. A total of 24 New Zealand rabbits were randomly divided into four groups of 6 rabbits each. Group 1 underwent a ligation of the lumbar artery at three levels (L1-L3), group 2 underwent a ligation of the lumbar artery at four levels (L1-L4) and group 3 underwent a ligation of the lumbar artery at five levels (L1-L5). The sham group contained 6 rabbits and did not receive ligation. TceMEP was recorded within 5 min of ligation and, 2 days later, motor function was assessed and the spinal cords were removed for histological examination. Following spinal cord injury, the relationship between variations in the TceMEP waveform and motor function and pathological damage was analyzed. It was observed that the amplitude of TceMEP began to decrease within 1 min of lumbar artery ligation and that the amplitude stabilized within 5 min. These amplitude changes that occurred within 5 min of different levels of permanent spinal cord ischemic injury were positively related to changes in motor function following recovery from anesthesia and 2 days after ligation. The Pearson correlation coefficient was 0.980 and 0.923 for these two time points, respectively (P<0.001). In addition, the amplitude changes were positively related to pathological damage, with a Pearson correlation coefficient of 0.945 (P<0.001). The results of the present study suggested that amplitude changes in TceMEP are particularly sensitive to ischemia. Ischemia may be detected within 1 min and the amplitude changes begin to stabilize within 5 min following ligation of the lumbar artery. The use of intraoperative monitoring of TceMEP allows for the detection of spinal cord ischemic injury with no time delay, which may allow for protective measures to be taken to prevent the occurrence of irreversible spinal cord injury.